Analisa Peramalan Penjualan Alat Kesehatan dan Laboratorium di PT. Tristania Global Indonesia Menggunakan Metode ARIMA - Lafnidita Farosanti (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2022)
Forecasting (forecasting) product sales in the business world provides significant benefits. A company can predict the number of sales in the future based on past data. PT Tristania Global Indonesia is a company that supplies customer requests in the form of medical and laboratory equipment in the Bali area and its surroundings. Transaction data owned by PT TGI has not been used optimally and is only a historical record so that further processing is needed. Through the transaction data, product sales forecasting analysis will be carried out using the Auto Regressive Integrated Moving Average (ARIMA) method with parameters p,d,q of 4,2,1. This parameter test was implemented on one of the categories of goods and city names, namely